Case report: Streptococcus pneumoniae pneumonia characterized by diffuse centrilobular nodules in both lungs - Zhang, Fangqi; Qin, Shaowen; Xia, Fei; Mao, Congzheng; Li, Long (Frontiers in Medicine, 2023)
Background Streptococcus pneumoniae (S. pneumoniae) is the most common pathogen in community-acquired pneumonia (CAP) and takes the form of lobar pneumonia as typical computed tomography (CT) findings. Various patterns of radiological manifestation have also been reported in patients with S. pneumoniae pneumonia; however, the appearance of diffuse centrilobular nodules in both lungs is rarely reported. Case presentation We report the case of a patient with a history of chronic lymphocytic leukemia (CLL) for 9 years who presented with new-onset fever, cough, excess sputum, and shortness of breath for 1 week. He was given intravenous antibacterial (cephalosporin) treatment for 4 days, but his condition did not improve and dyspnea became more serious. The chest CT indicated diffuse centrilobular nodules in both lungs at admission. Patient’s bronchoalveolar (BAL) fluid was sent for metagenomic next-generation sequencing, which only supported a diagnosis of S. pneumoniae infection. His condition improved gradually after antimicrobial treatment (moxifloxacin) and a follow-up CT showed that the diffuse centrilobular nodules in both lungs were absorbed completely. Conclusion This case highlights a rare CT presentation of S. pneumoniae pneumonia that should alert clinicians, so as to avoid taking unnecessary treatment measures.